Legal Interactions of Non-Muslims in Ottoman Sharia Courts: A Narrative Literature Review - Al-Khalidi, Fatima Kassab Hmoud (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to review key studies based on Ottoman records to explore issues concerning dhimmis and assess the legal rights they enjoyed. This study explores the role of Ottoman Sharī’a courts in protecting rights of non-Muslims, and provides a deeper understanding of legal interactions between them and Muslims in the Ottoman Empire. Furthermore, it seeks to assess legal status of non-Muslims and how it challenges or confirms the narrative of Islamic persecution. Methods: This study employs a descriptive-analytical and inductive approach to analyze the literature related to Ottoman court records, relying on multiple sources in both English and Turkish to understand how courts dealt with non-Muslim cases, with focus on documenting legal transactions and the role of non-Muslims in courts. Results: findings revealed that Ottoman Sharī’a courts played a vital role in documenting contracts and protecting legal rights of non-Muslims. Non-Muslims resorted to courts as plaintiffs and witnesses, reflecting their confidence in Ottoman judicial system. This study also showed that Ottoman judicial system was flexible and inclusive, contributing to the enhancement of social cohesion and interactions among various groups. Conclusions: The study concluded that Ottoman Sharī’a courts provided a unique model for managing religious and cultural diversity, reflecting Islamic tolerance and Ottoman state’s commitment to providing justice for all. These findings contribute to enhancing the historical understanding of Ottoman pluralism and offer contemporary legal lessons that can be utilized to manage diversity in modern states.